Targeting NaPi2b in ovarian cancer. (January 2023) - Banerjee, Susana; Drapkin, Ronny; Richardson, Debra L.; Birrer, Michael
Highlights: NaPi2b is expressed in malignant tissues with minimal expression in healthy tissues (85/85). NaPi2b is a targetable biomarker with stable expression throughout disease course (72/85). Archival tissue samples are sufficient to assess NaPi2b expression (68/85). Robust diagnostic assays can be developed to reliably detect NaPi2b expression (80/85). Early trials with NaPi2b antibody-drug conjugates in ovarian cancer are promising (83/85). Abstract: Novel biomarkers are needed to direct new treatments for ovarian cancer, a disease for which the standard of care remains heavily focused on platinum-based chemotherapy. Despite the success of PARP inhibitors, treatment options are limited, particularly in the platinum-resistant setting. NaPi2b is a cell surface sodium-dependent phosphate transporter that regulates phosphate homeostasis under normal physiological conditions and is a lineage marker that is expressed in select cancers, including ovarian, lung, thyroid, and breast cancers, with limited expression in normal tissues. Based on its increased expression in ovarian tumors, NaPi2b is a promising candidate to be studied as a biomarker for treatment and patient selection in ovarian cancer. In preclinical studies, the use of antibodies against NaPi2b showed that this protein can be exploited for tumor mapping and therapeutic targeting. Emerging data from phase 1 and 2 clinical trials in ovarian cancer have suggested that NaPi2b can be successfully detected in patient biopsy samples using immunohistochemistry, and the NaPi2b-targeting antibody-drug conjugate under evaluation appeared to elicit therapeutic responses. The aim of this review is to examine literature supporting NaPi2b as a novel biomarker for potential treatment and patient selection in ovarian cancer and to discuss the critical next steps and future analyses necessary to drive the study of this biomarker and therapeutic targeting forward.